Development of a Local Language Revitalization Model through a Student Team Based Project Integrated with the MBKM Program (Merdeka Belajar Kampus Merdeka) - R., Mantasiah; Yusri, Yusri; Amir, Johar; Daeng, Kembong (Universitas Negeri Makassar, 2022)
Abstract. This research aims to develop a local language revitalization model through a student team-based project which was implemented through sociolinguistics courses in tertiary institutions. The type of research used is Research and Development. The development model used is the ADDIE model. The local language revitalization model was validated by research respondents consisting of 3 sociolinguistic lecturers as expert validators and 30 students as user validators. The data analysis technique used is descriptive qualitative analysis and descriptive statistical analysis. The research findings show that there are 2 validation aspects that are in the good category, such as the completeness of learning materials and the availability of supporting learning media, while the other 3 aspects are in the very good category. Other findings show that the use of local language revitalization models through students’ team-based projects integrated with the MBKM program is proven to increase student understanding of the concept of local language revitalization and can increase students' positive language attitudes consisting of language loyalty, language pride, and language awareness